Favoriser le développement de la conscience épistémologique des étudiants lors de l’approprition de l’écrit glottodidactique en français et en polonais. Le cas des étudiants polonais d’ethnolinguistique - Orchowska, Izabela (Glottodidactica, 2020)
The paper is a reflection on the development of academic literacy skills in French and Polish while writing a diploma paper in glottodidactics by Polish third year ethnolinguistics students. The first part of the paper focuses on a diploma paper in glottodidactics as an important component of philological education at Adam Mickiewicz University in Poznań. Next, the author analyses the concept of epistemological consciousness and its impact on the development of student autonomy during the acquisition of glottodidactic discourse and glottodidactic knowledge as a specialist knowledge which they gain. The author’s conception, referring to writing research papers in line with the principles of glottodidactics as a research field, is based on the assumption that students should become aware of the epistemological specifics of glottodidactics and include them both in the form and the content of their diploma papers. Finally, the author discusses various stages in the development of students’ epistemological consciousness and looks into the processesthe supervisor needs to engage in for effective research supervision.